Sistem Rekomendasi Pekerjaan Menggunakan Content Based Similarity - Abdur Rouf; Yuliana Melita Pranoto; Endang Setyati (STMIK Banjarbaru, 2023)
Based on data from the Central Statistics Agency (BPS) it is stated that the data for people who did not have a job from August 2019 to August 2021 recorded an increase from 7104.42 to 9102.05, meaning that within 2 years people who did not have a job had increased significantly. This is caused by one of the factors, namely finding information on job vacancies which is difficult, users still have to choose one job at a time in accordance with their field of knowledge. By building a job recommendation system, users will find it easier to find suitable job information, the data used is obtained from 1120 (one thousand one hundred and twenty) alumni data which includes academic grades, non-academic scores, positions and companies obtained from alumni data from the Institute of Technology and Business Widya Gama Lumajang. Using a content-based similarity algorithm with machine learning techniques using the MLP classifier feature and several trials using different parameters in each experiment. In each experiment the researcher used 10 (ten) samples. The results of this trial the machine learning feature of the MLP classifier can be concluded to be able to provide an accuracy of 81% with a precision value of 0.77, a recall of 0.81 and an f1-score of 0.76.The results of this study are used by users or fresh graduates to get job recommendations in accordance with their field of study.Keywords: Content Based Similarity; Interaciton Based Relation; Job Recommendation System AbstrakBerdasarkan data Badan Pusat Statistik (BPS) menyebutkan bahwa data orang yang tidak memiliki pekerjaan dari agustus 2019 sampai dengan agustus 2021 tercatat naik dari angka 7.104,42 menjadi 9.102,05 artinya dalam kurun 2 tahun orang yang tidak memiliki pekerjaan mengalami kenaikan secara signifikan. Hal ini disebabkan oleh salah satu faktor yaitu mencari informasi lowongan pekerjaan yang sulit pengguna masih harus memilih satu per satu pekerjaan yang sesuai dengan bidang ilmunya. Dengan membangun sistem rekomendasi pekerjaan pengguna akan lebih mudah menemukan informasi pekerjaan yang sesuai, data yang digunakan diperoleh dari data alumni sebanyak 1.120 (seribu seratus dua puluh) yang mencakupi nilai akademik, nilai non akademik, jabatan dan perusahaan yang diperoleh dari data alumni Institut Teknologi Dan Bisnis Widya Gama Lumajang. Menggunakan algoritma content-based similarity dengan teknik machine learning fitur MLP classifier dan beberapa kali uji coba menggunakan parameter yang berbeda-beda pada setiap percobaannya. Pada setiap percobaan peneliti memakai 10 (sepuluh) sample. Hasil dari uji coba ini machine learning fitur MLP classifier dapat disimpulkan mampu memberikan akurasi sebesar 81% dengan nilai precision 0.77 recall 0.81 dan f1-score 0.76. Hasil penelitian ini digunakan oleh pengguna atau fresh graduate untuk mendapatkan rekomendasi pekerjaan yang sesuai dengan bidang ilmu.